Law and legal argumentation - Silva , Lídice Maria Lins; Furlan , Donizete Vaz; Santos, Luciano Rodrigues dos; Vasconcellos, Thaiza Kelly Gomes de (Seven Editora, 2024)
The main objective of this article is to approach the studies of argumentation and rhetoric, based from the classical world, to the contemporary argumentation of Robert Alexy's Discourse Theory in the field of Discourse Analysis. It discusses what is Argumentation in the General Sense and Classical Rhetoric, then the postulates of Argumentation in Legal Discourse are presented. To articulate the philosophical postulates of Socrates, Plato and Aristotle about the use of rhetoric and the contributions of the Analysis of the use of legal argumentation in the discourse with Robert Alexy, who will deal with legal argumentation in the discourse of judicial decisions from the philosophical point of view. The study arose from the factual analysis of argumentation by legal practitioners in the presentation of problems and in the decisions rendered by judges. This research presents the construction of the legal discourse that is based on legal argumentation so that it does not summarize the common argumentation used in the non-legal discourse. The bibliographic review method is used, consulting articles from indexed journals for its development. The research based on Alexy, and the legal discourses in decisions when based on legal argumentation are related to the field of Philosophy. DOI:https://doi.org/10.56238/sevened2024.010-013